PENGARUH AFTERSALES SERVICES DAN CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP LOYALITAS PELANGGAN PADA PT. DIPO INTERNATIONAL PAHALA OTOMOTIF, SISINGAMANGARAJA MEDAN - Alfonsius . (Sekolah Tinggi Ilmu Ekonomi Surya Nusantara, 2022)
The purpose of this research is to analyze the variables of Aftersales Services Customer Relationship Management on customer loyalty at PT. Dipo International Pahala Otomotif, Sisingamangaraja Medan. The questionnaire data was distributed to 72 customers of PT. Dipo International Pahala Otomotif, Sisingamangaraja Medan as the samples. The technique used is nonprobability sampling with purposive sampling technique. The data analysis technique used multiple linear regression analysis. The results show that (1) There is an positive influence of Aftersales Services and Customer Relationship Management on customer loyalty at PT. Dipo International Pahala Otomotif, Sisingamangaraja Medan. (2) There is an positive influence of Aftersales Services on customer loyalty at PT. Dipo International Pahala Otomotif, Sisingamangaraja Medan. (3) There is an positive influence of Customer Relationship Management on customer loyalty of PT. Dipo International Pahala Otomotif, Sisingamangaraja Medan